2012
DOI: 10.1210/jc.2011-3255
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipoproteins and Preeclampsia in Women with Type 1 Diabetes: A Prospective Study

Abstract: Context:In nondiabetic pregnancy, cross-sectional studies have shown associations between maternal dyslipidemia and preeclampsia (PE). In type 1 diabetes mellitus (T1DM), the prevalence of PE is increased 4-fold, but prospective associations with plasma lipoproteins are unknown. Objectives:The aim of this study was to define lipoprotein-related markers and potential mechanisms for PE in T1DM. Design and Settings:We conducted a multicenter prospective study in T1DM pregnancy. Patients:We studied 118 T1DM women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 46 publications
(56 reference statements)
6
24
0
1
Order By: Relevance
“…There is also some evidence of an association with maternal lipids. In women with type 1 diabetes, early pregnancy LDL-C was elevated in those who later developed preeclampsia (13). Conversely, in 184 women with GDM, maternal plasma cholesterol, LDL-C, HDL-C, and triglycerides did not differ in those who went on to develop preeclampsia (26).…”
Section: Maternal Obesitymentioning
confidence: 88%
See 1 more Smart Citation
“…There is also some evidence of an association with maternal lipids. In women with type 1 diabetes, early pregnancy LDL-C was elevated in those who later developed preeclampsia (13). Conversely, in 184 women with GDM, maternal plasma cholesterol, LDL-C, HDL-C, and triglycerides did not differ in those who went on to develop preeclampsia (26).…”
Section: Maternal Obesitymentioning
confidence: 88%
“…Women with well-controlled type 1 diabetes (mean HbA 1c 6.1%, 43 mmol/mol) had lipoprotein levels comparable to women with uncomplicated pregnancy, but those with poor control (HbA 1c 8.3%, 67 mmol/mol) at the time of delivery had higher triglycerides and VLDL and lower HDL 3 levels (12). Women with type 1 diabetes who go on to develop preeclampsia later in pregnancy have higher LDL-C and cholesterol than women with type 1 diabetes who do not develop preeclampsia (13).…”
Section: Preexisting Type 1 Diabetesmentioning
confidence: 93%
“…4,5 We have also shown higher plasma cholesterol-rich lipoprotein particles in early pregnancy (first and/or second trimesters) in women with T1DM who subsequently developed PE versus those who remained normotensive. 6 As part of our continuing efforts to identify early markers of PE in women with diabetes, we have explored the serum levels of soluble receptors for advanced glycation end-products (sRAGE) and several measures of advanced glycation end-products (AGE) in the same study cohort.…”
Section: Introductionmentioning
confidence: 99%
“…22 Basu A et al studied that early in pregnancy increased cholesterol rich lipoproteins were associated with subsequent preeclampsia similar to present study. 23 Bodnar et al shows irrespective of the obstetric score women with preeclampsia had higher BMI during pregnancy compared to normotensive pregnancies. 24 Sattar et al showed that the increased level of cholesterol and TGL in preeclamptic women.…”
Section: Discussionmentioning
confidence: 96%